Study on the impact of noise exposure on cognitive function - QIU Chunqin; HUANG Zhanrong; TANG Zhenzhen; PENG Lu (Guangxi Yike Daxue xuebao)
Noise, as one of the most common harmful environmental factors in our daily lives, can lead to hearing loss with prolonged exposure. More seriously, it can negatively affect cognitive function. The impact of noise exposure on cognitive abilities involves several aspects, including but not limited to reduced attention, memory, and learning and working capacity. Noise can trigger stress responses in the body, leading to elevated levels of stress hormones, which may adversely affect brain structure and function. Additionally, noise exposure may cause damage to the hippocampus, an important area of the brain responsible for memory and learning, and its damage can directly impair cognitive function. Noise exposure also induces oxidative stress and inflammatory responses, which can further damage brain cells, leading to a decline in cognitive abilities.